(untitled) (Bangladesh Journal of Psychiatry, 2021)
Assessment of parenting style would help to identify the risk and resilient factors in the parent child relationship. However, studies assessing the parenting styles in Bangladesh have not been conducted earlier. We aimed to determine the parenting styles and their association with different socio-demographic variables in Bangladesh. This cross-sectional study was conducted from 2017 to 2018 in three purposively selected schools. Data were collected from 349 parents having children of 6-16 years by using the Bangla parenting style and dimension questionnaire and analyzed in stata version 16. The results showed that, the mean age of the responded parents was 39.3 years, ranging from 22 to 62 years. Among the respondents, 36.96% (129) were male and the majority of the parents (44.98%) were housewives. Among the respondents, 84.8% (296) were predominantly authoritative, 8.6% (30) were predominantly authoritarian, 4.3% (15) were predominantly permissive and 2.3% (8) were undifferentiated/ uninvolved. Mothers had a significantly higher score in authoritarian domain score than the fathers (p=0.008). The comparison in parenting style revealed that authoritative parenting style was significantly higher in Bangla medium school (p=0.002). The study revealed authoritative parenting as the most widely practiced style in Bangladesh. This is the first attempt to ascertain the parenting styles in the country. Therefore, a prudential judgment and further studies are warranted to generalize the study results. Bang J Psychiatry 2021;35(2): 19-22